Relationship BetweenoMothers' Knowledge1of Balanced Nutrition and the NutritionalKStatus ofKToddlers at the Sialang Bangun Purba Community Health Center - Angraini, Salmi; Lindra Cahaya Putri Waruwu; Edarni Zebua; Dian Novita; Wira Maria Ginting (JURNAL KESMAS DAN GIZI (JKG), 2025)
The nutritional status of toddlers reflects their future health. Mothers' understanding of balanced nutrition plays a role in determining and providing appropriate food intake for toddlers. The purpose of this study was to determine the relationship between mothers' knowledge of balanced nutrition and the nutritional status of toddlers in the working area of the Sialang Bangun Purba Community Health Center. This study used a cross-sectional design with a quantitative approach. The sample consisted of 60 mothers with toddlers aged 0-5 years, selected using purposive sampling. Mothers' knowledge was obtained through questionnaires, while the nutritional status of toddlers was measured using anthropometry with weight-for-age as an indicator. Data analysis was performed using the Chi-Square test. The results showed that most mothers had a good level of knowledge (53.3%), and the majority of toddlers also had good nutritional status (53.3%). Based on the statistical test results, a p-value of 0.000 (p<0.05) was obtained, indicating a significant relationship between mothers' knowledge and toddlers' nutritional status. Thus, if mothers have a good understanding of balanced nutrition, their children's nutritional status will also be better. Therefore, nutrition education for mothers is essential to encourage the implementation of healthy eating patterns and prevent nutritional problems in toddlers.